Impact and associations of eosinophilic inflammation in COPD: analysis of the AERIS cohort. Issue 4 (12th October 2017) - Kim, Viktoriya L.; Coombs, Ngaire A.; Staples, Karl J.; Ostridge, Kristoffer K.; Williams, Nicholas P.; Wootton, Stephen A.; Devaster, Jeanne-Marie; Aris, Emmanuel; Clarke, Stuart C.; Tuck, Andrew C.; Bourne, Simon C.; Wilkinson, Tom M.A.
Eosinophilic inflammation in chronic obstructive pulmonary disease (COPD) predicts response to treatment, especially corticosteroids. We studied the nature of eosinophilic inflammation in COPD prospectively to examine the stability of this phenotype and its dynamics across exacerbations, and its associations with clinical phenotype, exacerbations and infection. 127 patients aged 40–85 years with moderate to very severe COPD underwent repeated blood and sputum sampling at stable visits and within 72 h of exacerbation for 1 year. Blood eosinophils ≥2% was prevalent at baseline, and predicted both predominantly raised stable-state eosinophils across the year (area under the curve 0.841, 95% CI 0.755–0.928) and increased risk of eosinophilic inflammation at exacerbation (OR 9.16; p<0.001). Eosinophils ≥2% at exacerbation and eosinophil predominance at stable visits were associated with a lower risk of bacterial presence at exacerbation (OR 0.49; p=0.049 and OR 0.25; p=0.065, respectively). Bacterial infection at exacerbation was highly seasonal (winter versus summer OR 4.74; p=0.011) in predominantly eosinophilic patients. Eosinophilic inflammation is a common and stable phenotype in COPD. Blood eosinophil counts in the stable state can predict the nature of inflammation at future exacerbations, which when combined with an understanding of seasonal variation provides the basis for the development of new treatment paradigms for this important condition. Blood eosinophil levels in COPD predict the nature of inflammation at future exacerbations and may guide therapy http://ow.ly/W10o30dNQiq